Effect of Using Sourdough Yeast And The Long Time of Final Proofing On The Physical Properties of Flashed Bread - Mohammad Wildan Almufarrij; Wardah; Dwi Cahyani, wahyukanti (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2024)
The use of natural yeast such as sourdough is an alternative choice in making bread. Apart from using yeast to produce good white bread, the final proofing time also affects the characteristics of bread. This research aims to determine the effect of using natural sourdough yeast and the final proofing time on the physical properties of white bread. This research was conducted at the integrated food laboratory of the Agro-Industry. The research design used was a one-factor completely randomized design with the independent variable used, namely the percentage of use of 0% natural sourdough yeast (instant yeast) , 15%, 30%, 45% and combined with final proofing treatment lengths of 45 minutes, 90 minutes, 135 minutes, 180 minutes, to obtain 16 treatments which were repeated 3 times. Analysis testing uses ANOVA (Analysis of Variance) with a significance level (P < 0.05) and SPSS 22 software. The results of the research show that the use of natural sourdough yeast and the long final proofing treatment have a significant effect on the physical quality of white bread in the form of dough riseability, porosity and softness of the bread. The use of natural sourdough yeast produced the highest value at the 45% level for the parameters of dough riseability of 58.631%, porosity of 54.851 pores and softness of white bread 154.262 mm/50g/10s. A good proofing time is 180 minutes resulting in a dough rising power of 62.905%, and 135 minutes for a porosity of 51.865 pores and softness of white bread 144.596 mm/50g/10s.